ANAESTHESIOLOGY AND INTENSIVE CAREMelatonin treatment in the prevention of postoperative delirium in cardiac surgery patients - Artemiou, Panagiotis; Bily, Boris; Bilecova-Rabajdova, Miroslava; Sabol, Frantisek; Torok, Pavol; Kolarcik, Peter; Kolesar, Adrian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Post-cardiac surgery delirium is a severe complication. The circadian rhythm of melatonin secretion has been shown to be altered postoperatively. Aim of the study : It was hypothesized that restoring normal sleeping patterns with a substance that is capable of resynchronizing circadian rhythm such as exogenous administration of melatonin may possibly reduce the incidence of postoperative delirium. Material and methods : This paper represents a prospective clinical observational study. Two consecutive groups of 250 consecutive patients took part in the study. Group A was the control group and group B was the melatonin group. In group B, the patients received prophylactic melatonin treatment. The main objectives were to observe the incidence of delirium, to identify any predictors of delirium, and to compare the two groups based on the delirium incidence. Results: The incidence of delirium was 8.4% in the melatonin group vs. 20.8% in the control group (p = 0.001). Predictors of delirium in the melatonin group were age (p = 0.001) and higher EuroSCORE II value (p = 0.001). In multivariate analysis, age and EuroSCORE II value (p = 0.014) were predictors of postoperative delirium. Comparing the groups, the main predictors of delirium were age (p = 0.001), EuroSCORE II value (p = 0.001), cardio-pulmonary bypass (CPB) time (p = 0.001), aortic cross-clamping (ACC) time (p = 0.008), sufentanil dose (p = 0.001) and mechanical ventilation (p = 0.033). Conclusions: Administration of melatonin significantly decreases the incidence of postoperative delirium after cardiac surgery. Prophylactic treatment with melatonin should be considered in every patient scheduled for cardiac surgery.